2018
DOI: 10.4103/japtr.japtr_317_18
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylurea and neuroprotection: The bright side of the moon

Abstract: Sulfonylurea (SUR) agents are the second and most used oral hypoglycemic drugs after metformin and they still as an imperative tool for most favorable of glucose control. SURs are used mainly in the management of Type 2 diabetes mellitus since; they are effective in the glycemic control and reduction of microvascular complications. First-generation SUR represents 3% of used oral hypoglycemic agents while second and third generations are used in about 25% in patients with Type 2 diabetes mellitus. Upregulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Another widely used class of glucose-lowering medication investigated for effects on the cerebrovascular system are sulfonylureas, which also have been suggested to have potential neuron protective effects in various neurological disorders [21,22]. However, its association with increased risk of hypoglycaemia could offset such benefits, as hypoglycaemia may increase the risk of cognitive impairment in type 2 diabetes [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another widely used class of glucose-lowering medication investigated for effects on the cerebrovascular system are sulfonylureas, which also have been suggested to have potential neuron protective effects in various neurological disorders [21,22]. However, its association with increased risk of hypoglycaemia could offset such benefits, as hypoglycaemia may increase the risk of cognitive impairment in type 2 diabetes [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…However, its association with increased risk of hypoglycaemia could offset such benefits, as hypoglycaemia may increase the risk of cognitive impairment in type 2 diabetes [ 23 , 24 ]. Preclinical studies suggest that sulfonylureas reduce brain infarct volumes and oedema and haemorrhagic conversion, and improve outcomes in rodent models of ischaemic stroke, mainly related to involvement of the sulfonylurea receptor 1 [ 22 ]. To date, however, there are no robust clinical data to support a benefit of either DPP-4 inhibitors or sulfonylureas on cognitive functioning [ 5 , 13 , 25 , 26 ], (see also literature review conducted up to 10 July 2020, electronic supplementary material [ESM] Table 1 ), and no direct comparisons have been performed.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective properties of diabetes drugs were first recognized by positive neurological effects in type 2 diabetes mellitus (T2DM) patients under treatment (Grant et al, 2011) and now in various studies for the treatment of different neurological conditions (Hussien et al, 2018;Rotermund et al, 2018;Erbil et al, 2019). A number of studies have demonstrated that diabetes drugs are indeed capable of entering the brain following systemic administrations and mediating a physiological response, e.g., metformin (Lv et al, 2012), sulfonylurea (SUR) (Simard et al, 2012), thiazolidine (Grommes et al, 2013), dipeptidyl peptidase-4 (DPP-4) inhibitors (Mousa and Ayoub, 2019), and glucagon-like peptide-1 receptor (GLP1-R) agonists (Hunter and Hölscher, 2012).…”
Section: Experimental and Animal Models Of Hiementioning
confidence: 99%
“…Sulfonylurea agents are the second oral hypoglycaemic drugs after metformin and they remain an imperative tool for glucose control (Thulé and Umpierrez, 2014). Recent studies demonstrated that sulfonylurea receptor 1 (SUR1) is involved in brain injury in rodent models of stroke (Hussien et al, 2018). The SUR drugs glibenclamide and glimepiride have neuroprotective effects (Ortega et al, 2013;Wang et al, 2019) and ameliorate cerebral stroke, spinal cord injury, premature encephalopathy, and TBI (Tosun et al, 2013).…”
Section: Sulfonylureamentioning
confidence: 99%
“…[ 3 ] It has been reported that pancreatic β-cells have low antioxidant resistance capacity; therefore, it is highly vulnerable to the risk of OS injury. [ 4 ] Amid different literature survey, various studies show that OS is concerned and linked with the complications of T2DM. Prolonged untreated OS in patients with T2DM leads to endothelial dysfunction (ED), insulin resistance (IR), impaired pancreatic β-cells, and lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%